2009
DOI: 10.1364/oe.17.002095
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state single photon sources: the nanowire antenna

Abstract: We design several single-photon-sources based on the emission of a quantum dot embedded in a semiconductor (GaAs) nanowire. Through various taper designs, we engineer the nanowire ends to realize efficient metallic-dielectric mirrors and to reduce the divergence of the far-field radiation diagram. Using fully-vectorial calculations and a comprehensive Fabry-Perot model, we show that various realistic nanowire geometries may act as nanoantennas (volume of approximately 0.05 lambda(3)) that assist funnelling the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
257
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(272 citation statements)
references
References 65 publications
15
257
0
Order By: Relevance
“…A similar trend in η col has been predicted for a dipole emitter embedded near the end of a semi-infinite dielectric nanowire 15,34 . It was shown that 34 , for a large nanopillar, most light is coupled into two guided HE 11 modes, one propagating upwards and the other downwards into the substrate. However, the upwards-propagating guided mode is mostly reflected back into the substrate by the top facet of the nanopillar.…”
supporting
confidence: 79%
“…A similar trend in η col has been predicted for a dipole emitter embedded near the end of a semi-infinite dielectric nanowire 15,34 . It was shown that 34 , for a large nanopillar, most light is coupled into two guided HE 11 modes, one propagating upwards and the other downwards into the substrate. However, the upwards-propagating guided mode is mostly reflected back into the substrate by the top facet of the nanopillar.…”
supporting
confidence: 79%
“…This point of view invokes an alternative strategy for optimizing light-matter coupling efficiency: one can modify the spatial mode of the atomic radiation to match the profile of the incident light beam, e.g., by employing parabolic [19] or planar [20] antennas. Similarly, it has been shown that a dielectric fiber with a subwavelength diameter can also channel the emission of an atom into its fundamental guiding mode [21,22] we generally refer to such a subwavelength waveguide antenna as a "nanoguide. "…”
mentioning
confidence: 99%
“…Interestingly, discussions of nanoguides have emerged somewhat in parallel to the tight focusing approach in different theoretical treatments [21][22][23][24] and experimental studies of glass nanofibers [25][26][27], plasmonic nanowires [28], photonic crystal waveguides [29,30], and even microwave transmission lines [31]. Moreover, scientists have investigated nonlinear optical effects in hollow-core fibers [32,33], although the mode in these structures is considerably less confined than in a nanoguide.…”
mentioning
confidence: 99%
“…10 At optimum waveguide conditions, the quantum dot emission is guided along the nanowire, adiabatically transferred to the far field and the larger fraction of this light is collected at small angles. In contrast, the emission of a dipole oriented along the nanowire axis couples very poorly to the fundamental waveguide mode.…”
mentioning
confidence: 99%